2009
DOI: 10.1016/j.ces.2008.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Granular temperature in a liquid fluidized bed as revealed by diffusing wave spectroscopy

Abstract: We report granular temperature and solid fraction fields for a thin rectangular bed (20×200 mm crosssection and 500 mm high) of glass particles (mean diameter of 165 m and density of 2500 kg/m 3 ) fluidized by water for superficial velocities ranging from 0.05U t , which is approximately double the minimum fluidization velocity, to 0.49U t , where U t is the particle terminal velocity estimated by fitting the Richardson-Zaki correlation to the bed expansion data. At superficial velocities below 0.336U t , the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
2
9
1
Order By: Relevance
“…A second decay in the IACF was observed at time scales of order 0.1 s (see, e.g., Figure 5a in Zivkovic et al18), which is consistent with the frequency of density waves in homogeneous fluidization (i.e., 4–8 Hz31). As this timescale is far greater than that associated with the granular temperature determination (i.e., 1–10 μs),18 the granular temperature measured here is unrelated to the oscillatory motion associated with the density waves.…”
Section: Methodssupporting
confidence: 78%
See 3 more Smart Citations
“…A second decay in the IACF was observed at time scales of order 0.1 s (see, e.g., Figure 5a in Zivkovic et al18), which is consistent with the frequency of density waves in homogeneous fluidization (i.e., 4–8 Hz31). As this timescale is far greater than that associated with the granular temperature determination (i.e., 1–10 μs),18 the granular temperature measured here is unrelated to the oscillatory motion associated with the density waves.…”
Section: Methodssupporting
confidence: 78%
“…A detailed description of the method used to determine the granular temperature in the liquid‐fluidized bed using DWS is provided in Zivkovic et al18 We provide here, however, a brief overview. IACFs were obtained by collecting and correlating 10 blocks of data of 30 s each.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The measurements were done at only one position, as our previous experiments found that the granular temperature varied very little with spatial position in the bed [20]. Measurements near the wall, and the top and bottom of the bed where variations may be expected were impossible due to experimental constraints [20,22]. Before each measurement the system was vibrated for at least 10 min, allowing the bed to reach a stationary state.…”
Section: Methodsmentioning
confidence: 99%